Energy Monitoring System Using Zigbee and Arduino - Govindarajan, R.; S.Meikandasivam, Dr.; D.Vijayakumar, Dr. (International Journal of Engineering and Technology, 2018)
The proposed concept provide a low cost Energy Monitoring System (EMS) using ZigBee wireless Communication with Arduino controller. It is used to monitor the electrical real time parameters without any wired network. In this paper we discussed about zigbee versus Arduino interfacing technique, which is used to reduce the more number of coding and get the energy meter reading in less range of delay time. The proposed concept is developedÂ  in order to achieve energy saving and provide the awareness to the residential, commercial and industrial consumer about the power utilization day to day with strong communication protocol and Â arduino controller with simple embedded coding. The objective of the system is, providing fast power communication between distribution and consumer with low cost and easy to interface.Â